2020
DOI: 10.1021/acs.jpclett.0c01870
|View full text |Cite
|
Sign up to set email alerts
|

Improving Stability of Lead Halide Perovskite via PbF2 Layer Covering

Abstract: The stability of perovskites is an urgent problem to be solved before commercialization. An ultrathin PbF2 layer covering the perovskite can be an effective strategy to improve the stability of the perovskite greatly. The perovskite/PbF2 interface (XPbI3/PbF2, X = Cs and MA) is constructed, and the structural and chemical properties are studied by first-principles calculations. The results show that PbF2 has better structural stability than the perovskites and can stabilize the octahedral frame of perovskite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Figure b (for Model 1) and Figure S3 (for the other models) show the difference in electron density between the PFPT3–perovskite interfacial system and the superimposed densities of PFPT3 fragments and perovskite. The electropositive Pb atom of the perovskite forms a surface bond with the electronegative F atom of PFPT3, where a partial electron transfer occurs from Pb to F, which corroborates the XPS results. A partial density of states (PDOS) analysis further supports Pb–F bond formation, as indicated by the broadened F-states near the Fermi level (Figure S4).…”
Section: Resultssupporting
confidence: 85%
“…Figure b (for Model 1) and Figure S3 (for the other models) show the difference in electron density between the PFPT3–perovskite interfacial system and the superimposed densities of PFPT3 fragments and perovskite. The electropositive Pb atom of the perovskite forms a surface bond with the electronegative F atom of PFPT3, where a partial electron transfer occurs from Pb to F, which corroborates the XPS results. A partial density of states (PDOS) analysis further supports Pb–F bond formation, as indicated by the broadened F-states near the Fermi level (Figure S4).…”
Section: Resultssupporting
confidence: 85%
“…Although electrons and holes do not recombine in the CsPb 2 Br 5, theCsPb 2 Br 5 acts as a protective layer, because the CsPb 2 Br 5 is stable under high temperature, high pressure, and high humidity. However, the stability of 3D perovskites is a problem for researchers. Previous studies reported that other materials like 2D perovskites, PF 2 , and so on are beneficial to improve the stability of 3D perovskites. The CsPb 2 Br 5 and the CsPbBr 3 have the same elemental composition, which can also inhibit the surface defects of CsPbBr 3 , such as V Br .…”
Section: Resultsmentioning
confidence: 99%
“…Their CBM mainly attributes to the Bi-6 p and I-5 p orbitals. Bader and electron localization function analyses (Figure S3 and Table S4) show an electronic structure intermediate between fully ionic and fully covalent bonding, similar in the character to the metal halide bonding in MAPbI 3 …”
Section: Resultsmentioning
confidence: 84%
“…The main features of the three structures are the co-existence of Cu−I, Bi−I bonds, and S4) show an electronic structure intermediate between fully ionic and fully covalent bonding, similar in the character to the metal halide bonding in MAPbI 3 . 38 The electronic band structures of the three polymorphs are presented in Figure 3, and the band gaps (E g ) calculated by the HSE06 method are presented in Table S4. The results show that P1̅ − III and P2 1 /m are indirect gap semiconductors with E g = 1.4 and 1.9 eV, respectively, while P1̅ − II is a direct gap semiconductor with E g = 2.0 eV.…”
Section: Resultsmentioning
confidence: 99%